A Supramolecular Trinuclear Nickel(II) Complex with Asymmetric Salamo-type Ligand: Synthesis and Crystal Structure - Dong, W.-K.; Meng, J.-L.; Zhang, X.-Y.; Zhao, M.-M.; Li, G.; Dong, X.-Y. (Asian Journal of Chemistry, 2013)
A supramolecular trinuclear Ni(II) complex, namely [NiL(EtOH)(μ-OAc)]2Ni·EtOH, has been synthesized through the complexation of nickel(II) acetate tetrahydrate with 5-methoxy-4'-bromo-2,2'-[ethylenedioxybis(nitrilomethylidyne)]diphenol (H2L). The Ni(II) complex comprises three Ni(II) atoms, two deprotonated L2- units, two acetate aions, two coordinated and one non-coordinated ethanol molecules. In the crystal structure, the terminal Ni(II) (Ni2 or Ni2#1) atom is located in the cis-N2O2 coordination cavity of the L2- units and coordinated to an oxygen (O7) atom from the μ-acetato anion and an oxygen (O8) atom from the coordinated ethanol molecule in the axial positions. Meanwhile, the central Ni(II) (Ni1) atom is completed by quadruple μ-phenoxo oxygen (O3, O4, O3#1 and O4#1) atoms from two L2- units and double μ-acetato oxygen (O6 and O6#1) atoms. All the Ni(II) atoms are hexa-coordinated, showing slightly distorted octahedral coordination arrangements. The Ni(II) complex is linked to form an infinite 2D layer supramolecular structure through intermolecular O-H···O, C-H···O and C-H···p hydrogen bond interactions.